2016
DOI: 10.1111/pbr.12356
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of Indian melon (Cucumis melo L.) landraces with special reference to disease and insect resistance loci

Abstract: This study was aimed to examine the genetic diversity and population structure of Indian melon landraces with special reference to disease and insect resistance loci. Thirty-six simple sequence repeat (SSR) markers along with seven markers at disease and insect resistance loci were used for this purpose on a panel of 91 accessions available at Indian Institute of Horticultural Research, Bengaluru, India. Model-based structure analysis revealed the presence of four groups that were consistent with the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
(71 reference statements)
2
4
0
Order By: Relevance
“…Similarly, Hu et al (2019) identified four clusters using cluster analysis, while their STRUCTURE analysis indicated three subpopulations, roughly corresponding to the varietal melon germplasm used in their study. Previous studies employing SSR markers in Indian melon accessions revealed two structural groups (K = 2) (Reddy et al 2016;Saha et al 2022), corroborated by PCoA clustering into two distinct groups. The study discovered 28 genotypes with admixed lines containing genetic material from another population (Falush et al 2003).…”
Section: Allelic Patterns Across Subpopulationssupporting
confidence: 55%
See 3 more Smart Citations
“…Similarly, Hu et al (2019) identified four clusters using cluster analysis, while their STRUCTURE analysis indicated three subpopulations, roughly corresponding to the varietal melon germplasm used in their study. Previous studies employing SSR markers in Indian melon accessions revealed two structural groups (K = 2) (Reddy et al 2016;Saha et al 2022), corroborated by PCoA clustering into two distinct groups. The study discovered 28 genotypes with admixed lines containing genetic material from another population (Falush et al 2003).…”
Section: Allelic Patterns Across Subpopulationssupporting
confidence: 55%
“…This extensive gene flow likely accounts for the prevalence of numerous admixed lines within the germplasm collection. The notable factors contributing to this high gene flow could be ongoing anthropogenic seed dispersal over time and space, crosspollination behavior, genetic drift, as well as natural and artificial hybridization between improved cultivars and local landraces, which may have facilitated the domestication of diverse and intermediate forms of melon (Reddy et al 2016). F ST serves as a genetic measure of population variation, with values exceeding 0.15 signifying significant differentiation (Frankham et al 2002).…”
Section: Allelic Patterns Across Subpopulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…have been utilized in melon landraces, for the study of genetic diversity, molecular fingerprinting of genetic material, and association with variable traits such as resistance to biotic and abiotic stresses. Forty-nine Indian landraces and varieties were studied using SSR markers, revealing beneficial alleles at loci conferring resistance to Fusarium wilt, downy mildew, powdery mildew, aphids, and viruses [ 142 ]. Using GBS sequencing, Pavan et al [ 143 ] detected 25,422 SNPs by examining 72 accessions of Apulia in Southern Italy, including landraces of a winter melon, namely chate melon, which is also known by the folk name of ‘Carosello’ and ‘Barattiere’ that was never characterized before.…”
Section: Application Of New Genomic Technologies In Landraces and Ind...mentioning
confidence: 99%